Cooperativism as a driving force for agricultural cooperatives that form part of the NODESS ecosystem in the Serdán Valley - González-Panzo, Barsimeo; Hernández-Osorio, Nadia Yasmín; Hernández Jiménez, José Pascual (Cooperativismo & Desarrollo, 2025)
The research analyzes the impact of cooperativism on the competitiveness of the agricultural entities that make up the NODESS ecosystem of the Serdán Valley. This study focuses on strengthening collaboration between organizations through the implementation of the cooperative model, integrating the Node for Sustainable Economic and Social Development (NODESS), and aims to promote sustainable development at the local level. Using a quantitative and correlational approach, data was collected through structured surveys from 213 active members of cooperatives, agricultural societies, and SMEs. The results, analyzed using Spearman's correlation, revealed a significant positive correlation between the level of cooperativism and the participants' perceptions of the social and solidarity economy. With a correlation coefficient of 0.630 (p < 0.01), these findings suggest that cooperativism not only strengthens the efficiency and productive capacity of the entities involved, but also promotes economic and social development in the Serdán Valley in line with the objectives of NODESS. This research highlights the importance of cooperativism as an organizational tool in rural communities, facilitating access to new markets, the exchange of knowledge, and increasing competitiveness in the agricultural sector. The study suggests that the cooperative model can play a crucial role in the sustainable growth of these organizations within the NODESS ecosystem, promoting local economic and social development.
Keywords: Cooperatives; Competitiveness; Social Economics; NODESS